Isolation and identification of proteolytic, amylolytic, lipolytic, and chitinolytic bacteria from shrimp waste - Sirvas Cornejo, Susana (2021)
Bacteria and microbial enzymes are biocatalysts and can be used as an alternative to industrial chemical processes. The present study focused on isolating and identifying bacterial strains from shrimp waste, that produce amylases, lipases, proteases and chitinases with potential use on shrimp waste treatment. Thirty-two bacterial strains were isolated, phenotypically characterized, and identified by the API system and the molecular analysis of the 16S rDNA. It was found that 28.13% of the isolated bacterial strains had amylolytic capacity, 87.50% lipolytic, 96.88% proteolytic and 28.13% chitinolytic capacity on agar plates with specific substrates. The genera Bacillus, Burkholderia, Ochrobactrum, Vibrio, Pseudomonas and Shewanella were identified. Bacteria with enzymatic capacities isolated in the present study, could be used to obtain by-products from shrimp waste as well as other industrial applications.